Collective action and property rights for poverty reduction: Introduction and overview - Mwangi, Esther; Markelova, Helen; Meinzen-Dick, Ruth S. (University of Pennsylvania Press, 2011)
The volume is organized in a way that aims to take the reader from an understanding of the central concepts examined in all the studies (poverty reduction, property rights, and collective action) to the application of these concepts in different contexts by means of various research methods. Part I (“Introduction and Conceptual Framework”) sets the stage with an introduction and Chapter 2, which provides a description of the conceptual framework and identifies the key research questions that are important when examining the institutions of collective action and property rights in poverty studies. Part II (“Risk Management and Market Access”) includes the Ethiopia-iddir, Philippines, and Kenya studies, the non- NRM case studies on collective action for risk management and market access. Part III (“Natural Resource Management”) includes Chapters 6-11, which deal with various aspects of resource management and access, as well as postconflict rebuilding. Part IV (“Synthesis and Conclusions”) synthesizes the findings of the case studies and reflects on the role of collective action and property rights in poverty reduction (Chapter 12), then points out the potential implications of these findings for policy, research, and practice (Chapter 13).